Early ultra-processed foods consumption and hyperactivity/inattention in adolescence - Campagnolo, Paula Dal Bo; Marin, Angela Helena; Vitolo, Marcia Regina; Ferreira, Ricardo Campos (Revista de Saúde Pública, 2024)
OBJECTIVE: To investigate the relationship between childhood consumption of ultra-processed foods and symptoms of hyperactivity/inattention in adolescents from São Leopoldo, a city in southern Brazil. METHODS: Data were collected at four distinct stages: when participants were 12-16 months old in 2001 and 2002 and later when they were 3–4, 7–8, and 12–13 years old. During the interview at 12–16 months, mothers were asked about the introduction of sugar in their child’s diet. Two 24-hour recall surveys were conducted with children aged 3–4, 7–8, and 12–13 years to assess their consumption of ultra-processed foods. At the age of 12–13 years, the participants completed the Hyperactivity/Inattention subscale of the Strengths and Difficulties Questionnaire (SDQ), which screens for mental health problems. RESULTS: Among the 173 adolescents, 22.5% exhibited hyperactivity symptoms. The consumption of ultra-processed foods in grams, kilocalories, and as a percentage of energy intake at 3-4 years old were found to be predictors of hyperactivity/inattention symptoms (RR: 0.81, 95%CI: 0.69–0.95; RR: 1.01, 95%CI: 1.00–1.02; RR: 1.02, 95%CI:1.01–1.02; RR: 1.25, 95%CI:1.04–1.51, respectively). CONCLUSION: The consumption of ultra-processed foods at an early age was associated with hyperactivity and inattention symptoms in adolescence.